Theme: Explanatory factors of the entrepreneurial intention of university students in Mali - Ousmane Mariko; Mahamadi Gaba (The Journal of Entrepreneurial Finance (JEF), 2022)
Graduate unemployment remains a concern for many African countries. However, in recent years there has been a growing interest in entrepreneurship among young people. The objective of this research is to study the entrepreneurial motivation of young graduates. Through primary data collected from students of the FSEG's entrepreneurial bachelor's degree programme and using a multiple linear regression model, it was found that: attitudes associated with behaviours have a positive and significant impact on the decision to become an entrepreneur. Social norms are determining factors in the explanation of entrepreneurial intention and finally, factors associated with perceived control contribute significantly to the explanation of entrepreneurial intention. In the light of these results, it would be wise for authorities to implement actions aimed at reinforcing the attitudes associated with student behaviour through entrepreneurial culture. In this case, a strong political determination is needed through legislation to make entrepreneurship a factor in bringing down unemployment among university graduates.
Keywords: 650; entrepreneurial intention; multiple linear regression; planned behaviour; students; Mali